Analisis Terhadap Hasil Penelitian Tentang Desain Model Pembelajaran ADDIE dan CTL Pada Pembelajaran PAI - Muhamad Ishaac; Muhammad Ramli (Universitas Islam Negeri Imam Bonjol Padang, 2024)
One of the learning designs and models often applied in PAI learning in several previous studies is the ADDIE design (analysis, design, development, implementation, evaluation), and the CTL (contextual teaching and learning) learning model. These designs and models are often used to improve the quality of Islamic religious education (PAI) learning. This article reviews and analyzes two previous journals regarding implementing the ADDIE design and the CTL model in PAI learning in high schools. The research method used is the Systematic Literature Review (SLR) method by identifying, evaluating, and interpreting relevant research results related to studies of ADDIE and CTL learning models. The results of the analysis show that the ADDIE design is implemented systematically and structured through five stages which can increase students' understanding of the material on Faith in the Last Day and apply it in life through behavior that is realized and visible at SMA Plus Tebar Ilmu Ciparay. Meanwhile, the CTL model is used to build collaboration, create fun learning, and improve students' critical and creative thinking skills.